Indonesian Consumer Price Index Forecasting Using Autoregressive Integrated Moving Average - Ishak, Shahnaz Salsabila; Abednego, Michael; Sari, Dian Maya; Sabila, Viyonisa Syafa; Khoirunnisa, Khoirunnisa; Alvionita, Mika; Muthoharoh, Luluk (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2023)
The Consumer Price Index is one of the indicators used to confirm financial success in inflation management. This study aims to help determine the CPI prediction value in Indonesia for the next twelve periods in a month using the ARIMA (Autoregressive Integrated Moving Average) method using the data from January 2015 to March 2022. The results obtained show that the best model that can be used for forecasting is the ARIMA model (2,1,2) with drift with Akaike's Information Criterion (AIC) values of 2190.84. The results of Indonesia's accurate CPI forecasting can be used to assess inflation management for policymaking in the context of controlling inflation.It can be concluded that Based on the analysis, the optimal ARIMA model for forecasting Indonesia's CPI is ARIMA (2,1,2) with drift, aiding in evaluating inflation management for policymaking